2016
DOI: 10.1186/s12889-016-3229-0
|View full text |Cite
|
Sign up to set email alerts
|

Assessing contraband tobacco in two jurisdictions: a direct collection of cigarette butts

Abstract: Background: The sale of contraband tobacco allows for tobacco tax evasion, which can undermine the effectiveness of tobacco tax policies in reducing the number of smokers. Estimates of the proportion of contraband vary widely as do the methods used to measure the proportion of contraband being smoked. The purpose of this study is to determine the proportion of contraband use in two different jurisdictions. Methods: A cross-sectional direct collection of cigarette butts was conducted in Peel and Brantford, Onta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“… 20 In addition, the inspection of discarded cigarette packs or cigarette butts can be used to determine whether all taxes have been paid. This approach has been recently used in France, 21 Canada, 22 23 the USA, 24 25 the UK 26 and Warsaw, Poland. 27 …”
Section: Introductionmentioning
confidence: 99%
“… 20 In addition, the inspection of discarded cigarette packs or cigarette butts can be used to determine whether all taxes have been paid. This approach has been recently used in France, 21 Canada, 22 23 the USA, 24 25 the UK 26 and Warsaw, Poland. 27 …”
Section: Introductionmentioning
confidence: 99%
“…To be informative, butt collections must protect against bias based on location. In their independent study of two municipalities, Stratton et al found a much higher proportion of contraband butts in the location closest to indigenous reserves 47. They further note that analysis of butts requires specific controls for error in identifying contraband and, unlike pack swap surveys, there is no opportunity to ask smokers if the purchase was tax-exempt or tax-evasion.…”
Section: Resultsmentioning
confidence: 99%
“…Developed from Merriman,27 Reuter and Majmundat,28 Ross3 and Stratton et al 47*Some studies used multiple methods.ITTP, illicit trade in tobacco products.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation